A Minimally Invasive Full Endoscopic Approach to Tibial Nerve Neurolysis in Diabetic Foot Neuropathy: An Alternative to Open Procedures. Issue 3 (24th August 2021) - Uemura, Tetsuji; Watanabe, Hidetaka; Yanai, Tetsu; Kawano, Hiroshige; Yoshida, Aya; Okutsu, Ichiro
Abstract : Background: Dellon et al. have reported that chronic nerve compression of the tibial nerve inside the tarsal tunnel, caused by diabetes mellitus, can be relieved following open decompression surgery. However, the large skin incision resulting from Dellon's procedure may cause wound healing problems. The authors report the possibility of a minimally invasive full endoscopic procedure. Methods: Operations were performed under local anesthesia without a pneumatic tourniquet. An anesthetic agent was applied at the proximal part of the flexor retinaculum of the foot, and a hypodermic needle was advanced into the tarsal tunnel. Tarsal tunnel pressure and blood circulation of the tibial nerve using indocyanine green assessment were measured preoperatively. One 1-cm portal skin incision was made at the anesthetized area and the Universal Subcutaneous Endoscope system was inserted into the tarsal tunnel. The flexor retinaculum, tibial nerve, blood vessels, and abductor hallucis muscle fascia were identified under endoscopic observation. After decompression of the tarsal tunnel, the authors measured tarsal tunnel pressure and blood circulation of the tibial nerve for analysis of the effectiveness of the endoscopic decompression during the procedure. Results: Fourteen operations were compiled and analyzed. Postoperative clinical status was improved based on the preoperative modified Toronto Clinical Neuropathy Score. The mean tarsal tunnel pressure dropped to 4.5 mmHg during surgery from the initial preoperative 49.4 mmHg in resting position. Endoscopic indocyanine green assessment showed more than 30 percent improvement of the vascularity surrounding the tibial nerve. Conclusion: The authors' minimally invasive full endoscopic procedure is a viable alternative approach for tarsal tunnel syndrome patients with diabetic foot neuropathy. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.